Special War and Terrorism: Review scientific paper - Alispahić, Bakir (Technium Social Sciences Journal, 2021)
Rapid and extreme development of human society causes a significant reduction of non-renewable resources, as well as the destruction of nature and the biosphere. Also, anarchy in international relations contributes to the mutual distrust of state actors who invest significant resources in primarily offensive systems. In such an environment, adaptation is the key to survival, and powerful and medium-powerful states often avoid open conflict with states of their own or higher rank, and take a series of actions in the domain/spectrum of Special War as a way to act invisibly, subversively in order to destroy enemies. Such an aggressive and unjust strategy allows the infliction of colossal damage to the enemy without its own losses or international sanctions. Terrorism, as an element of the Special War, is a powerful offensive weapon of aggressive and unjust states, which, avoiding direct and conventional conflicts and military targets, attack civilians as a vulnerable category. The goal of terrorist attacks in the overall strategy is not just to kill, but to cause psychological consequences that demoralize and destabilize the state and make it susceptible to future subversive action. Also, a special form of terrorism is genocide, which through organized, planned and systematic destruction of civilians, seeks to conquer certain territories and resources. This kind of inhumane act by an aggressive state is aided by other elements of the Special War, such as propaganda that deceives or covers up crimes committed. Identifying and taking measures and sanctions against aggressive states waging Special War is an imperative for world peace and equality, so a better understanding of this problem contributes to creating mechanisms for detecting aggressive measures of Special War and the states that implement them. The aim of this paper is to discuss the subversive power of Special War and the use of terrorism as an instrument for achieving unjust goals. Since the Special War is an action of ‘closed’ state institutions and the intelligence sector, and because it is considered a novelty in the research community, certain information is unavailable or partially unclear, which has limited the research.